Tackling local environmental challenges with livelihoods strategies: insights from small-scale farmers in the vulnerable region of Ghana - Bright Osei Boateng; Henry Mensah; Eric Kwame Simpeh; Patrick Opoku; Lilian Amponsaa Boateng (International Journal of Agricultural Sustainability)
Climate risks pose significant challenges to farmers' livelihoods, particularly in sub-Saharan Africa, where the complex interplay of factors intensifies the impact on small-scale farmers (SSFs). While there is a broad understanding of climate change's effects on agriculture, there is a need for deeper insights into the key determinants and preferences influencing SSFs' adaptation strategies in vulnerable regions to better inform agricultural policy and planning. Data were collected from 325 SSF randomly selected in Juaben Municipality, Ghana. Quantitative analysis was done using descriptive and inferential statistics, while qualitative data were analyzed through content analysis. The study identified shifting planting dates, altering farm operation timings and mulching as primary adaptation strategies. Significant associations were found between socio-economic factors and the adaptation strategies employed by SSFs, with the Relative Importance Index highlighting affordable tools, land ownership and access to fertile land as crucial for enhancing livelihoods and adaptation. The findings underscore the need for training programmes to equip extension officers with the knowledge to support SSFs in developing skills and efforts related to adaptation and viable livelihood options.